Can Uganda achieve SDG 6 on Water and Sanitation? - Budget Monitoring and Accountability Unit (Budget Monitoring and Accountability Unit, 2019)
During the 2015 United Nations Sustainable Development Summit, Uganda and 192 other United Nations (UN) member states unanimously agreed to the new global development framework: ‘Transforming our world - the 2030 Agenda for Sustainable Development. This Agenda is a plan of action for people, the planet and prosperity. Resolutions were made to “end poverty in all its forms”, to take bold and transformative steps to “shift the world on to a sustainable and resilient path” and to ensure that “no one will be left behind”. The 2030 Agenda established 17 Sustainable Development Goals (SDGs) and 169 global targets, relating to development outcomes and means of implementation, for the period 2015-2030. Each UN member state is expected to localize the global targets by designing a development agenda and policies that will accelerate the achievement of the SDGs by 2030. The existing national frameworks for implementing the SDGs in Uganda are: Vision 2040, second National Development Plan (NDP II), and Sector Development Plans among others.The SDG 6 - Ensure availability and sustainable management of water and sanitation for all, reflects the increased attention on water and sanitation issues in the global political agenda. The 2030 Agenda lists rising inequalities, natural resource depletion, environmental degradation and climate change among the greatest challenges of our time. It recognizes that social development and economic prosperity depend on the sustainable management of freshwater resources and ecosystems and it highlights the integrated nature of SDGs. This policy brief reviews the performance of some indicators of the water and sanitation sub-sector by end of June 2018 in reference to SDG 6.